Diagnostic accuracy of acute diverticulitis with unenhanced low‐dose CT. Issue 4 (20th May 2020) - Thorisson, A.; Nikberg, M.; Torkzad, M. R.; Laurell, H.; Smedh, K.; Chabok, A.
Abstract: Background: The aim of this study was to evaluate the diagnostic accuracy of unenhanced low‐dose CT (LDCT) in acute colonic diverticulitis in comparison with contrast‐enhanced standard‐dose CT (SDCT). Methods: All patients with clinically suspected diverticulitis who underwent LDCT followed by SDCT between January and October 2017 were evaluated prospectively. CT examinations were assessed for signs of diverticulitis, complications and other differential diagnoses by three independent radiologists (two consultants and one fourth‐year resident) using SDCT as the reference method. Sensitivity and specificity were calculated and Cohen's κ coefficient was used for agreement analyses. Results: Of the 149 patients included (mean age 66·7 years, M : F ratio 0·4), 107 (71·8 per cent) had imaging consistent with diverticulitis on standard CT. Sensitivity and specificity values for a diverticulitis diagnosis using LDCT were 95–99 and 86–100 per cent respectively, and respective values for identification of complications were 58–73 and 78–100 per cent. The corresponding κ values among the three readers for diagnosis were 0·984, 0·934 and 0·816, whereas κ values for complications were 0·680, 0·703 and 0·354. Of the 26 patients who presented with other causes of abdominal symptoms identified on standard CT, 23 were diagnosed correctly on LDCT. Missed cases included splenic infarction (1) and segmental colitis (2). Conclusion: The diagnostic accuracy of LDCT was high for the presence of acute diverticulitis. However, as signs of complicated disease can be missed using the low‐dose protocol, use of LDCT as a primary examination method should not preclude SDCT when complications may be suspected. Abstract : Unenhanced low‐dose CT (LDCT) is as accurate as contrast‐enhanced standard‐dose CT (SDCT) for detection of acute colonic diverticulitis. However, smaller complications, such as pericolic abscesses and small amounts of extraluminal air, can be missed. CT scan and diverticulitis Abstract : Antecedentes: Evaluar la precisión diagnóstica de la tomografía computarizada de dosis baja ( low‐dose computed tomography, LDCT) sin contraste frente a la TC con dosis estándar ( standard‐dose CT, SDCT) con contraste en la diverticulitis aguda de colon. Métodos: Todos los pacientes con sospecha clínica de diverticulitis aguda de colon a los que se realizó una LDCT seguida de una SDCT entre enero y octubre de 2017 se evaluaron prospectivamente. Tres radiólogos independientes (dos consultores y un residente de cuarto año) analizaron los signos de diverticulitis, complicaciones y otros diagnósticos diferenciales, utilizando la SDCT como método de referencia. Se calculó la sensibilidad y la especificidad, utilizándose el coeficiente κ de Cohen para los análisis de concordancia entre observadores. Resultados: De los 149 pacientes incluidos en el estudio (edad media 66, 7 años, varón/mujer 0, 4), 107 (71, 8%) presentaban unas imágenes compatibles con diverticulitis en la SDCT. La sensibilidad y la especificidad para el diagnóstico de diverticulitis con la LDCT variaban entre el 95‐99% y el 86‐100%, respectivamente. La sensibilidad y la especificidad para la identificación de complicaciones oscilaron entre el 58‐73% y el 78‐100%, respectivamente. Los valores κ entre observadores para el diagnóstico fueron del 0, 98, 0, 93 y 0, 82, respectivamente, mientras que para las complicaciones fueron del 0, 68, 0, 70 y 0, 35. De los 26 pacientes en los que la SDCT identificó otras etiologías como causa de sus síntomas abdominales, 23 fueron diagnosticados correctamente con la LDCT. Los casos con diagnóstico erróneo correspondían a un infarto esplénico y dos colitis segmentarias. Conclusión: La precisión diagnóstica de la LDCT fue alta para detectar una diverticulitis aguda. Sin embargo, el protocolo de dosis baja puede no identificar los signos de la enfermedad complicada. Por lo tanto, su utilización como método de exploración primario no debe excluir la SDCT cuando se sospechen complicaciones.